2023
DOI: 10.3390/pr11061664
|View full text |Cite
|
Sign up to set email alerts
|

Ketones in Low-Temperature Oxidation Products of Crude Oil

Abstract: Ketone compounds are oxidation products of crude oil in the in-situ combustion (ISC) process. Revealing the molecular composition of ketones can provide theoretical guidance for understanding the oxidation process of crude oil and valuable clues for studying the combustion state of crude oil in the reservoir. In this study, low-temperature oxidation (LTO) processes were simulated in thermal oxidation experiments to obtain thermally oxidized oil at different temperatures (170 °C, 220 °C, 270 °C, and 320 °C). A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The Hongqian heavy oil has a high biodegradation degree and high TAN . Previous study had shown that large amount acids could be produced in the simulated ISC process, which lead to an increase in TAN value .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Hongqian heavy oil has a high biodegradation degree and high TAN . Previous study had shown that large amount acids could be produced in the simulated ISC process, which lead to an increase in TAN value .…”
Section: Resultsmentioning
confidence: 99%
“…The Hongqian heavy oil has a high biodegradation degree and high TAN. 30 Previous study had shown that large amount acids could be produced in the simulated ISC process, which lead to an increase in TAN value. 27 Considering that high acid crude oil has corrosion problems on refinery processing facilities, 31 it is of great significance to deeply understand the changes in TAN and the molecular composition of acidic compounds in the produced oils.…”
Section: Characterization Of Methyl Esterificationmentioning
confidence: 97%